Pengaruh Gaya Kepemimpinan, Motivasi Kerja, Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT.Bersama Teman Sejahtera - Matsani, Matsani (Neolectura, 2023)
This study examines the impact of leadership style, work motivation, and work environment on employee performance at PT. BTS (Bersama Teman Sejahtera). Using a quantitative research approach, data were collected from employees through structured questionnaires. The findings reveal significant relationships between leadership style, work motivation, work environment, and employee performance. The results underscore the importance of effective leadership, intrinsic motivation, and conducive work environments in enhancing employee performance within the organization. The population consists of 50 employees, with the sample size also being 50 employees. Data collection methods include literature review and questionnaire surveys. Data analysis is conducted using Partial Least Square (PLS) version 3.0. The findings of this research indicate that Leadership Style does not have a significant influence on employee performance at PT. BTS. Work motivation positively influences employee performance at PT. BTS. Additionally, the work environment also positively affects employee performance at PT. BTS. Implications for management practices and future research directions are discussed.